The Model of Law Enforcement Based on Pancasila Justice - Arsyad Aldyan; Abhishek Negi (Lembaga Contrarius Indonesia, 2022)
The development of the current flow of law in Indonesia in the context of law enforcement is unquestionably still evident in the application of positivism in law enforcement, which, of course, with the application of legal positivism is enforced the law that is more important, if one considers that the philosophical goal of the law is the creation of justice, and so on. This is a declaration of Pancasila values in law enforcement in the Indonesian state. In some instances, it appears that the flow of positivism continues to exert a strong influence on law enforcement in Indonesia, which, of course, can affect the values of justice in law enforcement. As stated in Article 24 paragraph 1 of the Constitution of the Republic of Indonesia, in order to realize the Indonesian state as a rule of law, both law enforcement and justice must be properly enforced in the context of judicial power.